Service Delivery in the Lesotho Tourist Attraction Sector: Are Tourists Satisfied with the Service Provision? - Boitumelo Caroline Rasethuntsa (Profesional Muda Cendekia Publishing, 2021)
Tourism has emerged into an economic giant and an engine utilised by African countries to gain economic benefits. Because tourism is a diverse industry comprising of many subsectors, tourist attractions are regarded as a strategic area of the industry. This study aims to determine the features that attract tourists to Lesotho and establish whether the tourists are satisfied with the service quality provided at local tourist attractions. The study utilised qualitative research approach, and interviews were conducted to gain the insight information regarding the topic under investigation. The findings revealed that the Lesotho landscape and culture are features stimulating destination visitation. Also, the empirical results highlighted that tourist are dissatisfied with the local tourist attractions services including underutilisation of online services, unprofessionalism and lack of skills, under marketing of tourist attractions, and environmental sustainability mismanagement among others. Strategies for improvement are provided based on the findings to enable enhanced management of tourist attractions.